Spreading depolarizations cycle around and enlarge focal ischaemic brain lesions - Nakamura, Hajime; Strong, Anthony J.; Dohmen, Christian; Sakowitz, Oliver; Vollmar, Stefan; Sué, Michael; Kracht, Lutz; Hashemi, Parastoo; Bhatia, Robin; Yoshimine, Toshiki; Dreier, Jens P.; Dunn, Andrew K.; et al. (Brain, 2010)
How does infarction in victims of stroke and other types of acute brain injury expand to its definitive size in subsequent days? Spontaneous depolarizations that repeatedly spread across the cerebral cortex, sometimes at remarkably regular intervals, occur in patients with all types of injury. Here, we show experimentally with in vivo real-time imaging that similar, spontaneous depolarizations cycle repeatedly around ischaemic lesions in the cerebral cortex, and enlarge the lesion in step with each cycle. This behaviour results in regular periodicity of depolarization when monitored at a single point in the lesion periphery. We present evidence from clinical monitoring to suggest that depolarizations may cycle in the ischaemic human brain, perhaps explaining progressive growth of infarction. Despite their apparent detrimental role in infarct growth, we argue that cycling of depolarizations around lesions might also initiate upregulation of the neurobiological responses involved in repair and remodelling.
Gesehen am 05.05.2023